Skrajnie prawicowy terroryzm w Europie Wschodniej - Stempień, Marta Sara (Przegląd Wschodnioeuropejski, 2025)
Far-right movements are part of a “non-civil socjety” characterized by the acceptance of violence as a means of political struggle, racism and xenophobia, anti-state ideology and anti-egalitarianism. It seems that such movements should not find a place in the mainstream political scene of democratic countries. However, reality contradicts this (Płatek 2015). As early as 2001, representatives of the extreme right won seats in the parliaments of Eastern European countries, and a large part of the population of these countries considers far-right activists to be defenders of traditional values. The spatial scope of the research in this article covers the region of Eastern Europe, with the following countries abstracted from it: Bulgaria, the Czech Republic, Poland, Romania, Slovakia and Hungary. The subject of the research is the phenomenon of terrorism in the six mentioned countries and two distinguished groups: the “Visegrad countries” and the countries of the Black Sea region. The threat of terrorism in the countries surveyed remains relatively low compared to Western Europe. However, it should be remembered that the threat of endogenous terrorism may increase due to the exacerbation of social and political conflicts.